Analysis of Fadil Jaidi's Online Identity on TikTok : Analisis Identitas Online Fadil Jaidi di TikTok - Armawati, Dea; Juliananta Putra, Airlangga Cipta (Procedia of Social Sciences and Humanities, 2025)
The development of information and communication technology has facilitated the emergence of various social media platforms, including TikTok, which serves as a strategic tool for individuals and public figures to build their online identity. This study aims to analyze the strategies employed by Fadil Jaidi in constructing his digital identity through TikTok content. Using a descriptive qualitative approach, this case study explores elements such as authenticity, context management, and collaboration in shaping Fadil Jaidi's image. The findings reveal that Fadil successfully creates a relatable, consistent, and engaging persona through audience interactions and content reflecting familial values and humor. Despite challenges like context collapse and privacy risks, Fadil effectively leverages social media opportunities to strengthen his personal branding. This research provides insights into the dynamics of digital identity in an increasingly interactive social media era.